Reverberações do simbólico: ponderações em torno da cultura popular e de suas modulações midiáticas // REVERBERATIONS OF THE SYMBOLIC: REFLECTIONS ABOUT POPULAR CULTURE AND ITS MEDIA MODULATIONS - Silveira, Fabrício José Nascimento da (Contemporanea, 2012)
Abstract: Taking into account the distinct modalities of representation and modulation of the “popular” that reverberate in Brazilian media devices, especially in television, thearticle aims to deal with the following questions: how and to which degree the com-munication vehicles have been appropriating the meaning instances that characterize and define the ordinary man? Does popular culture resonate and reach some degreeof reverberation and visibility in the scope of the media sphere? What meanings andaccounts have been mobilized by media products, mainly the television ones, to alludeto what belong to the popular? To accomplish these goals, some theoretic and me-thodological strategies are employed, such as, to recover the main conceptual topicsthat have been traditionally evoked to address the symbolic universe that demarcatespopular culture, to identify how the popular have been incorporated and referencedby culture and media devices and, finally, to analyze how and to what measure this setof postulates transmute into keys for reading and understanding better the issues thatwere brought to the surface.Resumo: Atentando para as distintas modalidades de representação e de modulação do “popular” que reverberam no âmbito dos dispositivos midiáticos brasileiros, especialmente o televisivo, o presente artigo se propõe a responder as seguintes questões: de que maneira e até que ponto os veículos de comunicação têm se apropriado das instâncias de significação que caracterizam/definem o “homem do povo”? A cultura popular encontra ressonância e alcança algum grau de reverberação e visibilidade no âmbito da esfera midiática? Que sentidos ou representações têm sido mobilizados pelos produtos da mídia, sobretudo a televisiva, para se fazer alusão ao que é do povo? Para tanto, adota como estratégias teórico-metodológicas: recuperar os principais traços conceituais que tradicionalmente têm sido evocados para se reportar ao universo simbólico que demarca a cultura popular; identificar como o “popular” tem sido incorporado/referenciado pela cultura/dispositivos midiáticos; e, por fim, analisar como ou em que medida este conjunto de postulados se converte em chave de leitura para melhor compreendermos as indagações aqui levantadas.